Exploring Faculty Members Perceptions about Socially Accountable Medical Education Challenges: A Qualitative Content Analysis - Somayeh Akbari-Farmad; Soleiman Ahmady; Soleiman Ahmady; Mohammad Ali Hoseini (Kerman University of Medical Sciences, 2016)
Background & Objective: In recent decades medical education has been expanding as part of the higher education system in the world Due to the complexities of clinical education the effect of various environmental factors on and changes in clinical environment the importance of accountability to society and patients and socially accountable medical education (SAME) challenges the exploration of faculty members perceptions about SAME challenges is necessary Thus the aim of this study was to explore faculty members perceptions on the challenges of SAME Methods: This qualitative study was conducted using qualitative content analysis in Shahid Beheshti University of Medical Sciences Iran in 2014 Knowledge obtained through qualitative content analysis is based on the unique views of the participants and actual data of the text The participants were 8 faculty members who provided the most data on the fundamental factors effective on SAME (purposive sampling) Semistructured interviews were conducted with the participants and they were asked to describe their experiences of and views on SAME Data collection was continued until achieving data saturation Data collection and analysis were carried out simultaneously through consideration of trustworthiness Results: The main themes extracted in this study were defective education which is not communitybased lack of adequate commitment of teachers as role models lack of motivation in students and management problems and lack of resources Conclusion: The results of the present study illustrate the necessity for fundamental and comprehensive modification of training programs and improvement of their processes so that they can accommodate the communitys requirements Moreover there is need for strategies to increase motivation among teachers and students